Survey of Community, Crime, and Health, 1995, 1998 (United States) - Ross, Catherine E. ([Verlag nicht ermittelbar], 2006)
The Survey of Community, Crime, and Health (CCH) was conducted in 1995 and 1998 in Illinois to examine the relationship between neighborhood disadvantage and physical and mental health, (over and above individual socio-economic characteristics), in order to develop a measure of perceived neighborhood disorder and to explore its role in explaining that relationship. Interviews were conducted with 2,482 respondents and covered topics such as physical health, mental health, health behaviors, use of services, and sense of control. Also examined were social support, perceived neighborhood characteristics, neighborhood social support, and personal and household demographics. In addition to individual-level variables, Wave I of the CCH contains a number of community-level variables that were created from the 1990 STF Census data. Variable names starting with T are tract-level, variables starting with C are county-level, and variables starting with P are city-level.